2008
DOI: 10.1002/dvdy.21578
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression pattern of the four mitochondrial adenine nucleotide transporter ant genes and their roles during the development of Caenorhabditis elegans

Abstract: The adenine nucleotide transporter (ANT) mediates exchange of cytosolic ADP and mitochondrial ATP. Although most species contain more than one ANT family member, it is not known whether their roles in developmental processes are redundant or specific. Here, we show that the Caenorhabditis elegans genome encodes four candidate ant genes (ant-1.1, ant-1.2, ant-1.3, and ant-1.4). We have investigated their spatiotemporal expression patterns and discovered that, whereas ANT-1.1 is a ubiquitously expressed mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 55 publications
4
21
0
Order By: Relevance
“…(Supplementary Figure S5). In agreement with its mitochondrial localization, the subcellular localization of the GFP signal in these cells was mostly cytoplasmic and somewhat similar to that of the C. elegans mitochondrial adenine nucleotide transporter ANT-1.1 (36).
Figure 5.OSGL-1::GFP localizes to mitochondria.
…”
Section: Resultssupporting
confidence: 71%
“…(Supplementary Figure S5). In agreement with its mitochondrial localization, the subcellular localization of the GFP signal in these cells was mostly cytoplasmic and somewhat similar to that of the C. elegans mitochondrial adenine nucleotide transporter ANT-1.1 (36).
Figure 5.OSGL-1::GFP localizes to mitochondria.
…”
Section: Resultssupporting
confidence: 71%
“…ANT-1.1 is an essential mitochondrial adenine transporter that is ubiquitously expressed (Farina et al, 2008). Our data clearly discriminates between two classes of exon-exon junctions for ant-1.1 : on one hand three constitutive junctions for each of which ~6 million reads are found, and on the other hand 170 junctions supported by a number of reads ranging from 1 to 200,000.…”
mentioning
confidence: 61%
“…Experiments in the fruit fly Drosophila melanogaster demonstrate that lipid droplet associated proteins are required to support early development [2]. It is important to note that the fat accumulation defects are not necessarily direct effect of lipid droplets, for example, act-5 (RNAi) worms likely have poor nutrient absorption due to defects in intestinal microvilli [58]. A limitation of our study was that we identified relatively few lipid metabolism proteins.…”
Section: Discussionmentioning
confidence: 99%